2010
DOI: 10.4149/gpb_2010_02_203
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial function in heart and kidney of spontaneously hypertensive rats: influence of captopril treatment

Abstract: Abstract. Effect of captopril treatment on capability of heart and kidney mitochondria to produce ATP was investigated in spontaneously hypertensive rats (SHR). Heart mitochondria from SHR responded to hypertension with tendency to compensate the elevated energy demands of cardiac cells by moderate increase in mitochondrial Mg 2+ -ATPase activity, membrane fluidity (MF) and in majority of functional parameters of the mitochondria (p > 0.05). Significant increase exhibited only the oxygen consumption (QO 2 ; p … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…We also found that, although captopril could repair mitochondrial damage in myocardial cells of rats with heart failure, it did not affect the protein and mRNA levels of SIRT1, p-AMPK, and PGC-1α. Previous studies have confirmed the protective effect of captopril on myocardial cells (Mujkosová et al, 2010). A previous study suggested that captopril has a protective role by improving energy metabolism (Gvozdjáková et al, 1999) and weakening apoptosis (Lin et al, 2013).…”
Section: Discussionmentioning
confidence: 80%
“…We also found that, although captopril could repair mitochondrial damage in myocardial cells of rats with heart failure, it did not affect the protein and mRNA levels of SIRT1, p-AMPK, and PGC-1α. Previous studies have confirmed the protective effect of captopril on myocardial cells (Mujkosová et al, 2010). A previous study suggested that captopril has a protective role by improving energy metabolism (Gvozdjáková et al, 1999) and weakening apoptosis (Lin et al, 2013).…”
Section: Discussionmentioning
confidence: 80%
“…An opposite effect, i.e., increase in the MF of heart mitochondria, may be reached via increased formation of energy transition pores in mitochondrial membranes, induced by augmented intracellular calcium signaling (Ziegelhöffer et al 2009). Increase in MF was also identified as an endogenous compensatory response to diverse physiological and pathological impulses Mujkošová et al 2010;Waczulíková and Šikurová 2010). Numerous, often antagonistic modulatory influences, which may act simultaneously, have prevented determination of the precise normal physiological range of changes in MF of heart and kidney mitochondria.…”
Section: Discussionmentioning
confidence: 98%
“…Others indicated that captopril elicited an antioxidant effect [ 192 ]. In contrast, captopril treatment did not elicit any protective effect on mitochondrial function as evidenced by the decreased oxidative phosphorylation rate and lowered ATP production in heart and kidney of spontaneously hypertensive rats [ 257 , 258 ]. Accordingly, Kancirová et al demonstrated that in vitro captopril inhibited the ATP synthase activity, while in vivo it elicited no direct effect on mitochondrial bioenergetics [ 259 ].…”
Section: Mitochondrial Effects Of the Main Classes Of Drugs Used In C...mentioning
confidence: 99%